An analytical model for collinear cracks in functionally graded materials with general mechanical properties. (15th November 2015) - Pan, Haizhu; Song, Tianshu; Wang, Zhihai
Abstract: The crack problems of functionally graded materials (FGMs) with general mechanical properties are usually to solve analytically. In this paper, an analytical model for collinear cracks in FGMs with arbitrary mechanical properties is developed. In the model, the general mechanical properties of the FGM are approached by dividing it into some layers with continuous properties along the gradient direction. The problem is finally reduced to a group of singular integral equations which are solved by numerical method. The interaction between the collinear cracks is discussed. The influences of the nonhomogeneity constants and geometric parameters on the stress intensity factors (SIFs) are analyzed. Some important conclusions are drawn.